The shallow-water New Caledonia Drilliidae of genus Clavus Montfort, 1810 (Mollusca: Gastropoda: Conoidea) - Kilburn, Richard N.; Fedosov, Alexander; Kantor, Yuri (Zootaxa, 2014)
Species of the genus Clavus of the conoidean family Drilliidae that occur in the littoral and shallow waters of New Caledonia are here revised. This study is based primarily on recent expedition material from the Institut de Recherche pour le Développement (New Caledonia) and Muséum National d’Histoire Naturelle (France). A total of 22 species is recorded, of which eight are described as new.        New species: Clavus boucheti, Clavus delphineae, Clavus virginieae, Clavus picoides, Clavus squamiferus, Clavus devexistriatus, Clavus hylikos, Clavus maestratii;        New synonyms: Tylotiella Habe, 1958 = Clavus; Clavus leforestieri Hervier, 1896 = Pleurotoma obliquicostata Reeve, 1845; Pleurotoma mariei Crosse, 1869 = Pleurotoma lamberti Montrouzier, 1860; Clavus mighelsi Kay, 1979, new name for Pleurotoma acuminata Mighels, 1845, non J. Sowerby, 1816, was misidentified by Kay 1979; the lectotype of P. acuminata Mighels, 1845, is mangeliine. Clavus mighelsi sensu Kay 1979, is a synonym of Pleurotoma humilis E. A. Smith, 1879. It is suggested that Pleurotoma pulchella Reeve, 1845, sometimes treated as an Indo-Pacific species, may be a senior synonym of Fenimorea halidorema Schwengel, 1940, from the tropical western Atlantic. Nomen dubium: Pleurotoma mediocris Deshayes, 1863.